Pitting corrosion – Preferred chloride diffusion pathways in physical vapor deposited AlCrN coatings. (February 2023) - Hudak, O.E.; Bahr, A.; Kutrowatz, P.; Wojcik, T.; Bohrn, F.; Solyom, L.; Schuster, R.; Shang, L.; Hunold, O.; Polcik, P.; Heller, M.; Felfer, P.; et al.
Abstract: Pitting corrosion of sputtered and arc evaportaed fcc-AlCrN coated low-alloy steel substrates was studied in a 0.1 M NaCl solution, using a three-electrode-cell. Depending on the deposition technique, several diffusion mechanisms were identified by high-resolution techniques (i.e. APT, TOF-SIMS). For arc evaporated AlCrN, incoherently embedded macro-particles provided the majority of fast-track diffusion pathways and pit-initiation sites, while their pristine coating matrix proved protective against chloride inward diffusion. Contrarily, the more coarse-grained sputtered AlCrN morphology with a highly orientated crystal growth featured diffusion paths along column boundaries, where chloride permeated the coating structure and initiated pit formations at the coating-substrate interface. Graphical Abstract: Pitting mechanisms for (a) arc evaporated- and (b) sputtered AlCrN thin films on low alloy steel. ga1 Highlights: Arc evaporated AlCrN provides a diffusion barrier against chloride inward diffusion. Prevalent inter-columnar chloride diffusion in sputtered 001 textured coatings. Growth defects govern pitting behavior in arced- and sputtered AlCrN coatings.